Risk factors for constant glycemic variability in pregnant women: a case-control study - Grasiela Martins Barros; Lyvia da Silva Figueiredo; Priscilla Alfradique de Souza; Beatriz Paiva e Silva de Souza; Helen Campos Ferreira; Ana Carla Dantas Cavalcanti (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to identify the factors associated with pregnancy that influence constant glycemic variability. Method: a case-control study with random sampling. The medical records of 417 pregnant women were divided into case group (200 pregnant women with constant glycemic variability) and control group (217 pregnant women without constant glycemic variability). Data were collected from 2009 to 2015. Results: pregnant women aged 25 years and over, with family history of diabetes mellitus, with systemic arterial hypertension, overweightness or obesity, sedentarism and polycystic ovarian syndrome are more likely to present changes in blood glucose. Conclusion: The study demonstrated that risk factors associated with pregnancy increase the risk of constant glycemic variability. The findings will allow reassessment of the interventions during pregnancy, providing an increase in nursing care quality.